2015
DOI: 10.1021/acs.energyfuels.5b00868
|View full text |Cite
|
Sign up to set email alerts
|

Regenerable Sorbent with a High Capacity for Elemental Mercury Removal and Recycling from the Simulated Flue Gas at a Low Temperature

Abstract: To remove and recycle elemental mercury from flue gas, a serial of Ce–Mn binary metal oxides was prepared and tested as the regenerable sorbents for mercury capture. Ce0.5Mn0.5O y showed the best performance at 100 °C (about 5.6 mg g–1 adsorption capacity), and Ce–Mn binary metal oxides could adsorb more elemental mercury than MnO y . Furthermore, it was found that captured mercury can be released from the sorbent in the form of elemental mercury by heating to 350 °C. Meanwhile, the sorbent can be regenerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Consecutive sorption–desorption experiments were then performed at both 300 and 350 °C. In the latter case, the amount of recovered mercury was high, in agreement with previous reports …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Consecutive sorption–desorption experiments were then performed at both 300 and 350 °C. In the latter case, the amount of recovered mercury was high, in agreement with previous reports …”
Section: Resultssupporting
confidence: 92%
“…In the latter case, the amount of recovered mercury was high, in agreement with previous reports. 38 Figure 9a,b shows that on average, ∼66% of Hg 0 undergoing sorption in each cycle was desorbed upon the completion of each of the successive sorption−desorption cycles. With the number of cycles, the amount of desorbed Hg 0 is moderately increasing, as a result of the increasing Hg in 0 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that catalytic oxidation and chemical adsorption played an important role in the process of elemental mercury removal. Without ammonia chloride modified, the efficiency of Hg 0 oxidation is higher . As the ammonia chloride loading value increased, most of the mercury was captured by the samples, which were formed HgO and HgCl 2 and adsorbed on the surface of the samples.…”
Section: Resultsmentioning
confidence: 99%